Efficacy and safety of prophylactic intravenous calcium supplementation in patients with secondary hyperparathyroidism after parathyroidectomy: a retrospective study - Pan, Yao; Zhu, Jiaqi; Wu, Zhenglong; Wu, Dengfeng (Frontiers in Endocrinology, 2025)
ObjectiveSevere hypocalcemia is a common complication in patients with secondary hyperparathyroidism (SHPT) after parathyroidectomy (PTX). The necessity of postoperative prophylactic intravenous calcium supplementation and the corresponding strategies are controversial. This study aimed to analyze the efficacy and safety of prophylactic intravenous calcium supplementation after PTX.MethodsWe retrospectively reviewed the clinical data of 125 patients with SHPT who underwent PTX between January 2020 and December 2023. Patients were divided into prophylactic intravenous calcium supplementation group (group A, 94 cases) and non-prophylactic intravenous calcium supplementation (group B, 31 cases). The baseline characteristics, laboratory data, surgical outcomes of the two groups were compared. Binary logistic regression analysis was used to identify risk factors for severe hypocalcemia and hypercalcemia after calcium supplementation.ResultsThe incidence of severe hypocalcemia in group A (30 cases, 31.9%) was lower than that in group B (19 cases, 61.3%) (P = 0.004). Binary logistic regression analysis revealed that non-prophylactic intravenous calcium supplementation, high level of preoperative parathyroid hormone (PTH) and alkaline phosphatase (ALP), and low level of preoperative serum calcium were risk factors for severe hypocalcemia. Preoperative high level of ALP was a negative predictor for hypercalcemia after calcium supplementation.ConclusionsPostoperative prophylactic intravenous calcium supplementation, followed by dynamic dosage adjustments based on serum calcium levels, in addition to routine oral calcium and calcitriol supplementation, could significantly reduce the incidence of severe hypocalcemia without substantially increasing the risk of hypercalcemia.